Bridging migraine and psychosis: a neuropsychiatric review of shared dopaminergic mechanisms - Rithin Jacob Antony Rajan; Roshini Esther A (Frontiers in Neurology)
Migraine is increasingly recognized as a disorder with both neurological and psychiatric dimensions, with increasing evidence suggesting a potential link to psychotic symptoms through shared dopaminergic dysfunction. Both conditions exhibit dopamine receptor hypersensitivity, neurotransmitter imbalances, and altered cortical excitability, raising the question of whether migraineurs, particularly those with aura, may be more susceptible to transient psychotic-like symptoms. This review explores the neurobiological overlap between migraine and psychosis, focusing on shared pathophysiological mechanisms, neuroimaging findings, and clinical evidence. Neuroimaging studies have revealed that migraineurs exhibit altered dopamine receptor binding and reduced synaptic dopamine during attacks, whereas psychotic disorders are characterized by sustained dopaminergic hyperactivity. These observations support the hypothesis that dopaminergic dysregulation may predispose migraineurs to sensory–perceptual disturbances that occasionally resemble psychotic symptoms. Importantly, this overlap does not imply that migraine leads to psychosis but rather suggests that shared neurochemical dysfunction may transiently modulate perception. Future research should clarify this interaction to improve the early identification and management of neuropsychiatric manifestations in migraine patients.